Downregulation of Profibrotic Gene Expression by Angiotensin Receptor Blockers (Iranian Journal of Kidney Diseases, 2018)
Introduction. Chronic allograft nephropathy is characterized by interstitial fibrosis and tubular atrophy. The main players in the process of fibrosis are transforming growth factor-β (TGF-β) and miR-21 expression with a bidirectional interplay. This study aimed to evaluate the effects of angiotensin receptor type 1 antagonist, losartan, on peripheral blood and tissue expression of TGF-β and miR-21 and histologic findings in allograft biopsy in kidney transplant recipients. Materials and Methods. In a randomized controlled trial, 54 patients were enrolled and divided randomly into 2 groups. Group 1 was treated with a daily dose of 25 mg of losartan and group 2 was considered as control. Blood sampling was done at 48 hours posttransplantation and the 3rd and 6th months after transplantation for measurement of TGF-β RNA and miR-21. Protocol biopsy was performed at the 6th month posttransplantation for RNA extraction and histologic evaluation of interstitial fibrosis and tubular atrophy. Results. Although patients were not different initially, those who underwent treatment with losartan had lower miR-21 and TGF-β levels in circulating PBMCs, and there was a decreasing trend in peripheral blood TGF-β levels during the 6-month follow-up period. Tissue expression of miR-21 and TGF-β was also considerably lower among the losartan-treated patients at the time of tissue biopsy. Conclusions. Losartan treatment decreased the tissue expression of miR-21 and TGF-β and tissue fibrosis in kidney transplant patient, and it had a protective effect on allograft function and may delay chronic allograft dysfunction by reducing mediators of fibrosis.